Determinants of Remittance Inflows in Nepal: Evidence from Asymmetric Analysis NARDL - Gurung, Arjun (Tribhuvan University Journal, 2026)
Nepal is one of the most remittance-dependent economies in the world, and remittance inflows consistently account for over a quarter of GDP. The determinants of remittance inflows, particularly those related to the migration channel and the external macroeconomic environment, remain poorly understood. This paper addresses this gap by analyzing the asymmetric determinants of remittance inflows to Nepal from 1993 to 2024 using the Nonlinear Autoregressive Distributed Lag (NARDL) model. The NARDL bounds test is used to confirm the existence of the long-run cointegrating relationship between the variables. The analysis shows that a negative change in the exchange rate has a large and significant impact on remittance inflow, and geopolitical risk has a positive and significant long-run impact. The labor permit is positive, but marginally significant. In the short term, changes in GCC GDP and negative exchange rate movements have a strong negative impact on remittance inflows, and the error-correction term indicates that about 63.5 percent of short-term disequilibrium is corrected within one year. The Wald test is used to assess the statistical significance of asymmetry, thereby supporting a nonlinear framework. The core findings are supported by robustness checks using FMOLS, DOLS, and CCR, particularly for negative exchange rate changes, geopolitical risk, and labor permits. These findings suggest that exchange rate depreciation and geopolitical uncertainty are important channels determining remittance inflows in Nepal, and that policy actions should account for the asymmetry in their impacts.